Hereditary sensory and autonomic neuropathy type V: Report of a rare case - Ritesh Kalaskar; Ashita Kalaskar (Wolters Kluwer Medknow Publications, 2015)
Hereditary sensory and autonomic neuropathy (HSAN) type V is a rare inherited disease caused by a mutation in the neurotrophic tyrosine kinase receptor, type 1 gene located on chromosome 1 (1q21-q22). It is characterized by pain insensitivity, partial anhydrosis without mental retardation and unimpaired touch and pressure sensitivity. Self-mutilation injury involving the teeth, lips, tongue, ears, eyes, nose, and fingers are invariable feature of this disorder. The purpose of this paper was to discuss the diagnosis and oral management of 18-month-old girl with HSAN type V, having typical oral manifestation of bitten tongue and auto-extraction of primary teeth. Modified bite guard was given to the patient to prevent further self-mutilating injuries to the tongue.